Changes in smile morphometric indices following maxillary advancement and mandibular setback surgery in skeletal Class III patients - Farzanegan, Fahimeh; Hearvi, Farzin; Karrari, Mandana; Shafaee, Hooman; Vaezi, Touraj; Rashed, Roozbeh (Bangladesh Journal of Medical Science, 2019)
Objectives: The aim of this study was to evaluate the changes in smile morphometric indices following maxillary advancement and mandibular setback surgery in patients with skeletal class III malocclusion. Materials and Methods: Smile morphometric indices were measured on frontal rest and smile photographs of 15 female patients with skeletal Class III malocclusions before and three months after maxillary advancement and mandibular setback surgery. Pre- and post-surgery measurements were compared. Results: The amount of left and right commissural height, philtrum height, and maximum upper incisor show at rest did not change significantly three months after surgery (p>0.05). The amount of maximum upper and lower incisor show, interlabial gap, smile width and index, buccal corridor ratio, gingival display, and smile arc on the frontal smile photographs didn’t showstatistically significant difference before and after surgery (P>0.05). Conclusion: Orthognathic surgery in patients with skeletal Class III malocclusion had no significant effect on rest and smile parameters from the frontal view. Bangladesh Journal of Medical Science Vol.18(2) 2019 p.216-221